Utilization of Chinese medicine for respiratory discomforts by patients with a medical history of tuberculosis in Taiwan - Su-Tso Yang; Yi-Rong Lin; Mei-Yao Wu; Jen-Huai Chiang; Pei-Shan Yang; Te-Chun Hsia; Hung-Rong Yen (BMC, 2018)
Abstract Background Tuberculosis (TB) is one of the world's major communicable infectious diseases, and it still imposes a great health burden in developing countries. The development of drug-resistant TB during the treatment increases the treatment complexity, and the long-term pulmonary complications after completing treatment raise the epidemic health burden. This study intended to investigate the utilization of Chinese medicine (CM) for respiratory symptoms by patients with a medical history of TB in Taiwan. Methods We analyzed a cohort of one million individuals who were randomly selected from the National Health Insurance Research Database in Taiwan. The inclusion criteria of patients (n = 7905) with history of TB (ICD-9-CM codes 010-018 and A02) were: (1) TB diagnosed between January 1, 1997 and December 31, 2010 (2) 18 years old or over (3) Clinical records for at least 2 months with complete demographic information (4) Record of treatment with first-line TB medication prescriptions. CM users for conditions other than respiratory discomforts (n = 3980) were excluded. Finally, a total of 3925 TB patients were categorized as: CM users for respiratory discomforts (n = 2051) and non-CM users (n = 1874). Results Among the 3925 subjects, 2051 (52.25%) were CM users, and 1874 (44.753%) were non-CM users. Female patients and those who were younger (18-39 y/o) and who lived in urbanized areas relatively tended to be CM users (p < .0001). Most of the CM users (1944, 94.78%) received Chinese medicines. The most commonly prescribed herbal formulas and single herbs were Xiao-Qing-Long-Tang and Radix Platycodonis (Jie-Geng), respectively. The core pattern of Chinese medicines for TB patients consisted of Ma-Xing-Gan-Shi-Tang, Bulbus Fritillariae Thunbergii (Bei-Mu), Radix Platycodonis (Jie-Geng) and Semen Armeniacae (Xing-Ren). Conclusions The use of CM is popular among patients with a medical history of TB complicated with long-term respiratory discomforts in Taiwan. Further pharmacological investigations and clinical trials are required.